Physicochemical and functional properties of arrowroot (Maranta arundinacea L.) starch - Leister, Dianne M.; Luna, Myrna Benita Z. (Quezon City College of Home Economics, University of the Philippines Diliman, 2018)
The physicochemical, and functional properties of arrowroot (Maranta arundinacea L.) starch (AS) produced in Marinduque, Philippines were characterized. Commercially-available cassava (Manihot esculenta) starch (CS) was used as a reference sample. The AS was found to be predominantly comprised of large oval granules with some small round ones, having an average particle size of 22.27 ± 1.70μm. It also was found to be composed of 8.9885 ± 0.1775%dry basis moisture, 34.5 ± 0.3% amylose, 0.11 ± 0.02% crude protein, 0.0877 ± 0.0035% total fat, and 145.0 ± 1.3ppm phosphorus. It exhibited a limited solubility and swelling power, possibly due to its large granule surface-area, high amylose content, and stable crystalline structure. These characteristics may have, then, contributed to its higher pasting temperature of 78.7 ± 0.5°C, low peak viscosity of 4226 ± 10cP, high final viscosity of 3514 ± 9cP, and low enthalpy of gelatinization of 299.49 ± 6.61J/g. Moreover, a low initial AS paste clarity of 36.4632 ± 0.9278%T650nm and a high rate of retrogradation during refrigerated storage (6.7422 ± 0.1809%T650nm/day) were observed. It also demonstrated a possible freeze-thaw stability and a slow rate of syneresis. AS was found to have significantly different properties from CS, except for its thermal properties; thus, resulting in differing possible applications. The observed properties of AS showed its potential in improving the consistency and textures, and handling of numerous products; such as confectionaries, gelled products, low-moisture snacks, Japanese harusame and Chinese rice vermicelli noodles, opaque sauces and gravies, and edible films. On the other hand, the properties observed in CS made it appropriate for white bread, clear fruit fillings and jellies, soft elastic noodles (Japan udon, Korea dried salted), minimally stirred and heated products, and refrigerated products, among others. A follow-up research on these possible applications may be performed to validate these inferences, together with the determination of the effects of shear conditions on AS and its interaction with potentially common food ingredients during processing. Moreover, further characterization of its other granule components and properties; and implementation of this research on a wider geographical scale would contribute to the development of a more comprehensive technical profile of locally-produced AS.
Thesis Classification: P
Thesis (B.S. in Food Technology)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Arrowroot; Arrowroot starch